Community's Perception of Post-Timah Mining Land Management as Aik Nibung ARD Garden Agro-Ecotourism in Badau Village - Nurida, Nurida; Evahelda; Fournita Agustina (Jurnal AGRISEP, 2023)
The development of Aik Nibung agro-ecotourism ARD Garden in Badau Village is a post-tin mining management business. This activity cannot be separated from the mainstay role of farmers in this management. This study aimed to identify various forms of business management of post-tin mining land by leading farmers and to describe community perceptions of post-tin mining land management in Badau Village. This research is a case study with a descriptive research method and is analyzed qualitatively using a Likert scale. Sampling was done purposively (purposive sampling) with a total of 30 respondents. Data was collected through questionnaires, observations, interviews, and documentation. The results showed that: 1) The business managed by farmers is the mainstay in developing the Aik Nibung agro-ecotourism area ARD Garden, namely celocia, sunflower and button flower gardens, horticultural plant cultivation and tilapia fish cultivation; 2) The community's perception of pre-management of post-tin mining land is in agreement with an index coefficient value of 78.2%. Community perceptions of post-mining land management agree with an index coefficient value of 78.7% and community perceptions of successful post-mining land management strongly agree with an index coefficient value of 83.17%. With an average index coefficient value of 80.02% at the level of strongly agree.